Efek Penambahan Kuning Telur Pada level Yang Berbeda Dalam Pengencer Spermax Terhadap Kualitas Semen Beku Babi Landrace: Effect of Adding Different Levels of Egg Yolk in Spermax Diluent on The Quality of Landrace Boars' Frozen Semen - Tako, Alfonia Inna; Nalley, W Marlene; Setyani, Ni Made Paramita; Hine, Thomas Mata (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2025)
Background: The benefits of frozen semen can improve the genetic quality of the offspring, the wide distribution of superior genetics to various locations even in distant areas. Purpose: The purpose of this study was to determine the optimal level of egg yolk in spermax diluent for the preservation of frozen semen of landrace boars. Methods: The design used was a completely randomized design consisting of four treatments with four replications each, namely: P1 = Spermax + 5% egg yolk, P2 = Spermax + 10% egg yolk, P3 = Spermax + 15% egg yolk, and P4 = Spermax + 20% egg yolk. Each treatment diluent was supplemented with 6% glycerol. Semen was diluted in the base diluent and stored for 2 hours at room temperature (27–28 °C). Next, the semen was centrifuged at 2000 rpm for 10 minutes, the supernatant was discarded, and the sediment was re-diluted. The semen was then evaluated for sperm motility, viability, and abnormalities, packaged in 0.5 mL straws, and equilibrated for 2 hours at a temperature of 3–5 °C. The semen was re-evaluated and frozen on the surface of liquid nitrogen at a distance of 10 cm for 10 minutes, then stored in a container filled with liquid nitrogen for 24 hours. The frozen semen was subsequently evaluated for motility, viability, abnormalities, and recovery rate. Results: The results of the study did not have a significant effect (T> 0.05) with the highest values in each treatment after thawing being motility (T3 = 28.75 ± 11.08%), viability (T4 = 47.52 ± 18.14%), abnormality (T1 = 9.84 ± 2.05%) and recovery rate (T3 = 35.93%). Conclusion: Addition of egg yolk with levels of 5%, 10%, 15% and 20% in the spermax diluent produces the same quality of frozen landrace boar semen.